2005
DOI: 10.1007/s00418-005-0066-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of surfactant proteins in type II pneumocytes of newborn, 14-day old, and adult rats: an immunoelectron microscopic and stereological study

Abstract: Surfactant proteins (SP) have an important impact on the function of the pulmonary surfactant. In contrast to humans, rat lungs are immature at birth. Alveolarization starts on postnatal day 4. Little is known about the distribution of SP during postnatal alveolarization. By immunoelectron microscopy, we studied the distribution of SP-A, SP-D, SP-B, and precursors of SP-C in type II pneumocytes before, near the end and after alveolarization and in mature lungs. We determined the subcellular volume fractions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…Immunohistochemistry of lung tissue (25,42) and of isolated cells by light microscopy (24, 41) has demonstrated SP-A in type II cells, but the lamellar bodies generally appear as empty vesicles that fail to label with anti-SP-A antibody. Studies at the electron-microscopic level using immunogold techniques have produced similar results: goldlabeled anti-SP-A antibody could be localized to the lamellar body membrane, but with few exceptions, very little gold labeling was observed within the lamellar body contents (12,27,33,34,38). It has been recognized that this relatively poor detection of SP-A may be due to various technical issues (17,38).…”
Section: Discussionmentioning
confidence: 78%
“…Immunohistochemistry of lung tissue (25,42) and of isolated cells by light microscopy (24, 41) has demonstrated SP-A in type II cells, but the lamellar bodies generally appear as empty vesicles that fail to label with anti-SP-A antibody. Studies at the electron-microscopic level using immunogold techniques have produced similar results: goldlabeled anti-SP-A antibody could be localized to the lamellar body membrane, but with few exceptions, very little gold labeling was observed within the lamellar body contents (12,27,33,34,38). It has been recognized that this relatively poor detection of SP-A may be due to various technical issues (17,38).…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, after segmental allergen challenge in patients with asthma the BALF contained increased SP-D but decreased SP-A values [24]. Decreased SP-A levels have also been found in BALF of asthma patients [42], in asthmatic BN rats after OVA sensitization and challenge by inhalation of an aerosol of 5% OVA [43] and in the BALF of sensitized BALB/c mice after allergen challenge [20, 44]. An increase of SP-D was consistently described in animal models [21, 22, 25, 44].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that the ability for rats to be born at term with anatomically immature lungs is largely due to the production of surfactant at birth. In contrast to human lungs, it has been shown that all four surfactant proteins (SP-A, -B, -C, and -D) can be detected in the type II pneumocytes in newborn rat lungs (49). In humans, the pulmonary surfactant system matures between 29 and 32 wk of gestation, which coincides with the saccular stage of lung development (52).…”
mentioning
confidence: 99%